Behaviour of Market Arrivals and Prices of Pearl Millet in Rajasthan - Sharma, Shirish; Singh, I.P. (Journal of Rural Development, 2016)
The present study was devoted to an analysis of behaviour of market arrivals and prices of pearl millet in Rajasthan. In Nagaur market, the arrivals in the peak period were maximum during last 10 years (2000-01 to 2009-10). These were in the range of about 55.91 (2003-04) to 79.92 per cent (2008-09) of the total arrivals. In Jodhpur market, the arrivals of pearl millet followed more or less the same pattern as in Nagaur. In Jaipur market, the arrivals in peak period were maximum. The maximum arrivals were in the peak period followed by mid-period and lean period. The seasonal indices analysis of arrivals and prices revealed that when major portion of the produce was received in the market, the prices were at the lowest. The correlation between arrivals and price in Jodhpur market was positive and statistically significant. This positive and significant correlation coefficient could be attributed to the off-season supplies of pearl millet which fetch higher prices. Trend analysis of arrivals of pearl millet in the selected markets of the State shows that the trend values of arrivals in Jaipur, Jodhpur and Nagaur showed an increasing trend over the years.